Novel Proteasome Assembly Chaperone mutations in PSMG2/PAC2, cause the autoinflammatory interferonopathy, CANDLE/PRAAS4 - de Jesus, Adriana A. (J Allergy Clin Immunol, 2019)
Chronic Atypical Neutrophilic Dermatosis with Lipodystrophy and Elevated temperature (CANDLE) is a rare autoinflammatory interferonopathy caused by additive loss-of-function mutations in proteasome genes. Mutations in the proteasome chaperone, PSMG2/PAC2 are a novel cause of CANDLE.